KESESUAIAN LATIHAN MEMBACA BUKU NETZWERK A1 DENGAN KURIKULUM 2013 - HANINDYA PUTRI, DIAZ; IMAM SAMSUL, SUWARNO (LATERNE, 2018)
In the process of learning a foreign language exercises are needed to achieve learning goals. Netzwerk A1 book has a lot of materials and exercises with levels (Niveau) A1. Exercises must be in accordance with the 2013 curriculum, so it can be used in German language learning. The problem formulation of this research is whether the exercises contained in the Netzwerk A1 book are in accordance with the 2013 curriculum. This research uses a qualitative descriptive method. The Data was collected from reading exercises in Netzwerk A1 of Taskbook section in chapters 4,8, and 10. The data then analyzed to draw conclusions. The aspects analyzed were the theme, vocabulary, and structure from the 2013 curriculum. Based on the results of this research, the reading exercises in the Netzwerk A1 book were mostly in accordance with the 2013 curriculum. But some exercises still did not have suitability. Keywords: Reading Skills, Exercise, Netzwerk A1